Advancing the design and modelling processes for high performance electrical machines - Al-Timimy, Ahmed Abdul Al-Kareem Hussen (2019)
The implementation of an integrated oil pump and drive motor (where no mechanical coupling between the motor and pump is required) is a very attractive solution for various industries, especially where high performance requirements are important, such as for the aerospace industry. As in many applications, high power density and high efficiency are very important design objectives. However, to achieve such objectives while keeping the overall weight of the electrical machine to minimum values is very challenging and requires an optimal machine design with a detailed knowledge of power losses. To address these aspects, this thesis aims to improve the machine performance through accurate modelling by considering often overlooked aspects during the development process of electrical machines. To achieve this goal, the first stage of the project involved the analysis, design and optimisation of a high performance, high power density electrical machine for directly-coupled pump application. The second stage has shown how accurate machine models that include the effects of machining processes required to produce the finished product (e.g. the stator core) and the effects of in-active component (e.g. rotor endcaps), can be achieved and used to provide a more accurate estimation for the machine performance than with the traditional methodologies. A prototype machine based on the first stage of this project is manufactured and experimentally tested. This machine was then used as a vessel for the second stage of the work. The main contribution of this work is the investigation and verification of the effects on the accuracy of design models due to 1) the detrimental effects of machining processes of the stator core and 2) the detrimental effects of leakage fluxes flowing in the inactive materials/components of the machine. This knowledge is then used to inform the future machine designer on how to take into consideration these aspects during the design of electrical machines.